Negative pole piece and battery

By designing a multi-layered active material layer in the negative electrode sheet of the lithium-ion battery and setting a recess at an appropriate depth, the problem of lithium-ion battery being extracted during high-speed charging is solved, and the rate performance and cycle performance of the battery are improved.

CN222785294UActive Publication Date: 2025-04-22HUIZHOU LIWINON NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420602851.2
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-03-27
Publication Date
2025-04-22
Estimated Expiration
2034-03-27

AI Technical Summary

Technical Problem

The existing lithium-ion batteries are easy to remove lithium when charging at high rates, and it is difficult to effectively control the performance of the pole sheet while improving the rate performance and cycling performance.

Method used

A negative electrode sheet is designed, including a current collector, a first active material layer and a second active material layer that are successively coated. The graphitization degree of the first active material layer is greater than that of the second active material layer, and a plurality of recesses are provided in the thickness direction of the current collector. The recesses penetrate through the second active material layer and extend to the inside of the first active material layer, and the depth of the recesses is controlled to satisfy a specific relationship.

Benefits of technology

By improving the conductivity of the first active material layer and the electrolyte wetting of the second active material layer, the migration speed of lithium ions and the rate performance of the battery are improved, the lithium-ion evolution phenomenon during high-rate charging is reduced, and the charging and discharge capacity of the battery is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222785294U_ABST
    Figure CN222785294U_ABST
Patent Text Reader

Abstract

The utility model belongs to the technical field of batteries, and particularly relates to a negative pole piece and a battery. The pole piece comprises a current collector, and a first active substance layer and a second active substance layer which are sequentially coated on the surface of the current collector and have different graphitization degrees, so that the graphitization degree of the first active substance layer is greater than that of the second active substance layer; the lithium ion transmission speed of the first active material layer which is infiltrated with electrolyte poorly can be improved, and the rate capability of the battery is improved; the lithium ion battery further comprises a plurality of concave parts which are uniformly distributed, and the concave parts penetrate through the second active material layer and extend into the first active material layer, so that the first active material layer and the second active material layer simultaneously participate in lithium ion transmission through the concave parts, the charging and discharging capability of active materials at all positions is ensured, and the performance of the battery cell is improved; and the depth of the concave part is moderate, so that the battery cell can bear higher charging rate without lithium precipitation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model belongs to the technical field of batteries, and in particular relates to a negative electrode sheet and a battery. Background Art

[0002] With the rapid development of new energy vehicles and large-scale energy storage industries, people have put forward higher requirements on the fast charging performance, cycle performance and other properties of lithium-ion batteries. At present, in order to meet the high energy density requirements of lithium-ion batteries, it is mostly achieved by increasing the thickness and compaction density of the active material layer, which leads to a longer migration path of lithium ions in the active material layer in the direction perpendicular to the current collector, a longer electrolyte transmission path, an increased internal resistance, and poor fast charging performance. Therefore, it is necessary to improve the structure of the electrode.

[0003] At present, the main method is to drill holes in the active material layer so that the electrolyte can directly enter the active material layer, shorten the migration path of lithium ions, improve the rate performance and cycle performance of the battery, and reduce lithium deposition on the electrode surface. However, the structure of the graphite in the hole will be damaged during the drilling process, thereby changing the OI value and other parameters of the graphite, affecting its electrochemical properties. Lithium deposition is likely to occur in the hole during high-rate charging. In addition, the different graphitization degrees of the pole pieces and the depth of the holes will affect the lithium deposition in the holes. Often, after increasing the hole depth to improve the rate performance and cycle performance, the battery is prone to lithium deposition during high-rate charging. After reducing the hole depth, the rate performance and cycle performance are reduced, and the performance of the pole piece cannot be effectively controlled.

[0004] Based on this, it is urgent to invent a negative electrode plate and a battery to solve the above-mentioned technical problems. Utility Model Content

[0005] One of the purposes of the utility model of the present application is to provide a negative electrode plate, which can not only improve the rate performance of the battery, but also prevent lithium from being easily deposited when the battery is charged at a high rate, thereby ensuring the charge and discharge capacity of the battery.

[0006] The technical solution of the utility model to solve the above technical problems is to provide a negative electrode plate, including a current collector and a first active material layer and a second active material layer sequentially coated on the surface of the current collector and having different graphitization degrees, and the graphitization degree of the first active material layer is greater than the graphitization degree of the second active material layer;

[0007] It also includes a plurality of evenly distributed concave portions, wherein in the thickness direction of the current collector, the plurality of concave portions penetrate the second active material layer and extend into the first active material layer;

[0008] The average thickness of the first active material layer is D1, the average thickness of the second active material layer is D2, and the depth of the concave portion is D, and the relationship between them satisfies: D2≤D<D2+1 / 2D1.

[0009] Specifically, the graphitization degree of the first active material layer (2) is P1, and the graphitization degree of the second active material layer (3) is P2, and the relationship between them satisfies: 0.9<P2<P1; the depth D of the concave portion satisfies: D2≤D<D2+1 / 3D1.

[0010] Specifically, the volume of the material removed from the recess is less than or equal to 20% of the volume of the entire negative electrode sheet.

[0011] Specifically, the volume of the material removed from the recess is greater than 5% of the volume of the entire pole piece.

[0012] Specifically, the recesses are arranged as a regular structure or an irregular structure, and the distance between two adjacent recesses is less than 2.5 mm.

[0013] Specifically, the recess is configured as a circular, square, elliptical or conical regular structure.

[0014] Specifically, when the concave portion is configured as a circular regular structure, the aperture of the concave portion is less than 80 μm.

[0015] Specifically, the depth D of the concave portion is 10 μm to 50 μm.

[0016] Specifically, the surface of the current collector is also coated with a functional layer adjacent to the first active material layer.

[0017] The beneficial effects of the utility model are:

[0018] The utility model arranges a first active material layer and a second active material layer stacked on each other, and ensures that the graphitization degree of the first active material layer is greater than that of the second active material layer, thereby improving the conductivity of the first active material layer close to the current collector (that is, compared with the second active material layer, the first active material layer has poor electrolyte wettability), reducing resistance, and facilitating the deintercalation of lithium ions. The layered structure of graphite is conducive to the migration of lithium ions. The high graphitization degree can increase the migration speed of lithium ions and improve the rate performance of the battery. The depth of the recess is controlled to satisfy D2≤D<D2+1 / 2D1, so that the first active material layer can participate in lithium ion transmission through the recess with the second active material layer at the same time, ensuring the charge and discharge capacity of the active material at each position, improving the performance of the battery cell, and the depth of the recess is moderate so that the battery cell can withstand a higher charging rate without lithium precipitation.

[0019] The second purpose of the utility model of the present application is to provide a battery, comprising any of the negative electrode plates described above. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation on the present invention. In the drawings:

[0021] Figure 1 It is a schematic diagram of the side cross-sectional structure of the negative electrode sheet of the utility model;

[0022] Figure 2 It is a schematic diagram of the side structure of the negative electrode sheet of the utility model;

[0023] Figure 3 It is a schematic diagram of the side structure of the negative electrode sheet of the utility model;

[0024] Figure 4 It is a schematic diagram of the side structure of the negative electrode sheet of the utility model;

[0025] Figure 5 It is a schematic diagram of the top view of the negative electrode sheet of the utility model;

[0026] Figure 6 It is a schematic diagram of the top view of the negative electrode sheet of the utility model;

[0027] Figure 7 It is a schematic diagram of the top view of the negative electrode sheet of the utility model;

[0028] Wherein: 1-current collector; 2-first active material layer; 3-second active material layer; 4-recess; 5-functional layer DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application. Unless otherwise defined, all technical and scientific terms used in this article have the same meaning as those generally understood by technicians in the technical field of this application. The terms used in this article in the specification of this application are only for the purpose of describing specific implementation methods, and are not intended to limit the present application.

[0030] like Figure 1As shown, the applicant has found that when laser drilling is performed on the active material layer of the negative electrode plate to shorten the migration path (or transmission path) of lithium ions and reduce the transmission resistance of lithium ions, lithium deposition on the electrode surface can be reduced. However, those skilled in the art have found that when the battery is in a high-rate charging state, the position of the aforementioned hole (that is, the concave portion 4 described below) is prone to lithium deposition and grows along the hole to the surface of the active material layer of the negative electrode material. In order to prevent lithium deposition in the hole, the depth of the hole needs to be reduced. However, after reducing the depth of the hole, the electrolyte wettability is poor at a deeper depth and the lithium ion diffusion coefficient is smaller, and the lithium ion transmission resistance is larger, which is not conducive to the deintercalation of lithium ions, and the rate performance is reduced (the rate performance is the ratio of the 2C rate discharge capacity of the battery cell at room temperature to the 0.2C rate discharge). In order to improve the rate performance, the electrode is set to a multilayer structure, wherein the first active material layer 2 close to the current collector 1 has a deeper depth and a smaller lithium ion diffusion coefficient, poor electrolyte wettability, and a larger lithium ion transmission resistance, which is not conducive to the deintercalation of lithium ions. The deintercalation and extraction of lithium ions, and the rate performance are low, and an active material with a higher degree of graphitization is used; the first active material layer 2 uses an active material with a high degree of graphitization to improve conductivity, reduce resistance, and is beneficial to the deintercalation and extraction of lithium ions. The layered structure of graphite is beneficial to the migration of lithium ions. A high degree of graphitization can increase the migration speed of lithium ions and improve the rate performance of the battery; in order to ensure that the second active material layer can fully play its role in improving the rate performance and the cycle performance, the depth of the recess 4 is controlled to satisfy D2≤D<D2+1 / 2D1, so that the first active material layer 2 can participate in the lithium ion transmission through the recess 4 and the second active material layer 3 at the same time, which can ensure the charge and discharge capacity of the active material at each position and improve the performance of the battery cell, and the depth of the recess 4 is moderate so that the battery cell can withstand a higher charge rate without lithium precipitation.

[0031] The present invention will be further described in detail below in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0032] Combination Figure 1 As shown, the present application provides a negative electrode plate, including a current collector 1 and a first active material layer 2 and a second active material layer 3 which are sequentially coated on the surface of the current collector 1 and have different graphitization degrees, and the graphitization degree of the first active material layer 2 is greater than the graphitization degree of the second active material layer 3; the negative electrode plate also includes a plurality of evenly distributed recesses 4, in the thickness direction of the current collector 1, the plurality of recesses 4 penetrate the second active material layer 3 by a laser punching process and extend to the inside of the first active material layer 2; the average thickness of the first active material layer 2 is D1, the average thickness of the second active material layer 3 is D2, the depth of the recess 4 is D, and their relationship satisfies: D2≤D<D2+1 / 2D1.

[0033] Among them, the depth D of the concave portion 4 satisfies D2≤D<D2+1 / 2D1, the concave portion 4 penetrates the second active material layer 3 and extends to the inside of the first active material layer 2, so that the concave portion 4 will make the high-graphitization active material of the first active material layer 2 and the low-graphitization active material of the second active material layer 3 participate in lithium ion transmission at the same time, ensure the charging capacity of the individual active materials, achieve the improvement of the charging capacity, and increase the active surface area of ​​the electrode, reduce the impedance during the cycle, and increase the infiltration of the electrolyte, thereby increasing the cycle life. During high-speed charging and discharging, the pore tortuosity of the electrode is reduced, and the lithium ion diffusion coefficient is increased, thereby improving the battery energy density and the battery rate performance. The depth of the concave portion 4 will not be too deep to cause lithium deposition during high-rate charging of the battery; the first active material layer 2 and the second active material layer 3 have different graphitization degrees and satisfy the first active The design that the degree of graphitization of the material layer 2 is greater than that of the second active material layer 3 can improve the rate performance of the battery. The depth of the first active material layer 2 close to the current collector 1 is deeper and the lithium ion diffusion coefficient is smaller, the electrolyte wettability is poor, the lithium ion transmission resistance is larger, it is not conducive to the deintercalation of lithium ions, and the rate performance is low; the use of active materials with higher graphitization degrees can improve conductivity, reduce resistance, and be beneficial to the deintercalation of lithium ions. The layered structure of graphite is beneficial to the migration of lithium ions. High graphitization degree can increase the migration speed of lithium ions and improve the rate performance of the battery; and the second active material layer 3 is arranged on the surface of the electrode and penetrated, so the lithium ion diffusion coefficient is larger and the charge and discharge performance is good. Using active materials with lower graphitization degrees, and because the second active material layer 3 is penetrated and more active materials are lost, using active materials with lower graphitization degrees can reduce the loss of graphite and save costs.

[0034] like Figure 3 As shown in FIG. 1 , when D=D2, the damage to the first active material layer with a high degree of graphitization is minimal. However, this is not easy to achieve in terms of process. Figure 2 As shown, preferably, the depth D of the recess 4 satisfies: D2≤D<D2+1 / 3D1. When the depth of the recess 4 satisfies this range, the process difficulty is moderate, the damage to the first active material layer is reduced, and the proportion of the damaged first active material layer with low graphitization degree is increased, which can improve the utilization rate of the high-graphitization active material with higher cost.

[0035] Preferably, the graphitization degree of the first active material layer 2 is P1, and the graphitization degree of the second active material layer 3 is P2, and the relationship between them satisfies: 0.9<P2<P1; when the graphitization degrees of the first active material layer 2 and the second active material layer 3 are both greater than 0.9, the electrode can meet the conductivity and lithium ion extraction requirements of most batteries.

[0036] like Figure 4As shown, in some embodiments, the surface of the current collector 1 is also coated with a functional layer 5 adjacent to the first active material layer 2. In the preparation of the battery pole piece, there is often not only an active material layer, but also a functional layer 5 for improving the conductivity of the contact position between the active material and the current collector 1, a functional layer 5 for improving the viscosity between the current collector and the active material, and a functional layer 5 for other effects.

[0037] Preferably, the volume of the material removed from the recess 4 is less than or equal to 20% of the volume of the entire negative electrode plate, so as to prevent excessive removal of active material from causing damage to the structure of the active material and facilitating lithium deposition.

[0038] Preferably, the volume of the material removed from the recess 4 is greater than 5% of the volume of the entire electrode, so that enough material of the first active material layer 2 is in direct contact with the electrolyte, thereby improving the infiltration of the electrolyte into the active material.

[0039] In some embodiments, in order to make the recess 4 have a better effect of improving the lithium ion diffusion coefficient for the active material at a deeper depth near the current collector 1, and to make the depth of the recess moderate and not easy to deposit lithium, preferably, the depth D of the recess 4 satisfies: when D2<1 / 3(D1+D2), 1 / 3(D1+D2)≤D, and the depth D of the recess 4 is 10μm~50μm.

[0040] Preferably, the distance between two adjacent recesses 4 is less than or equal to 2.5 mm, which can avoid the distance between the recesses 4 being too large. In the area between the adjacent recesses 4, the lithium ion diffusion coefficient is slightly improved, and the charge and discharge performance cannot be improved.

[0041] like Figure 4-6 As shown, in some embodiments, the recesses are arranged as regular structures or irregular structures, and the spacing between two adjacent recesses 4 is less than 2.5 mm. The recesses 4 can be formed by different methods such as laser etching, chemical etching, and plasma gas etching, and these etchings cause the shapes of the recesses 4 to be regular or irregular.

[0042] Preferably, the recess 4 is configured as a circular, square, elliptical or conical regular structure, which are shapes that can be easily formed by common laser etching or chemical etching.

[0043] Further preferably, when the recess 4 is set to a circular regular structure, the aperture of the recess 4 is less than 80 μm, so that the spacing between adjacent recesses in all directions is uniform, which has a better diffusion coefficient improvement effect under the same volume of removed material.

[0044] Further preferably, the interval between the plurality of recesses is less than or equal to 2.0 mm. Preferably, the materials of the first active material layer 2 and the second active material layer 3 both include carbon-based materials.

[0045] The following is an example of a battery manufactured in combination with the negative electrode sheet of the present application:

[0046] Example 1

[0047] Positive electrode sheet: The active material lithium cobalt oxide, the conductive agent acetylene black, the conductive carbon nanotubes, and the binder polyvinylidene fluoride (PVDF) are fully dispersed and evenly coated on the aluminum current collector in an N-methylpyrrolidone solvent system in a weight ratio of 97.8:0.6:0.4:1.2, and then cold-pressed and sliced ​​to obtain the positive electrode sheet.

[0048] Negative electrode sheet: The negative electrode active material with a graphitization degree of 95% and the negative electrode active material with a graphitization degree of 99% were mixed with sodium methyl cellulose and styrene-butadiene rubber (SBR) emulsion in a weight ratio of 97.7:11:12 to prepare two negative electrode active material slurries, which were simultaneously coated on the copper current collector. The thickness of the surface active material with a graphitization degree of 95% was 15 μm and the thickness of the bottom active material with a graphitization degree of 99% was 55 μm. Then, the negative electrode sheet was obtained by cold pressing and striping. The laser drilling parameters of the electrode sheet: depth 20 μm.

[0049] Isolation film: The PE surface is coated with a ceramic mixture as an isolation film.

[0050] Electrolyte: Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a volume ratio of 1:1:4:4, and then fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0051] Preparation of a full battery: The positive electrode sheet, separator, and negative electrode sheet are wound or stacked to produce a bare cell, which is then packaged and injected with electrolyte to produce a finished lithium-ion battery.

[0052] The batteries of Examples 1 to 3 and Comparative Examples 1 to 3 were prepared in a similar manner to Example 1, and the specific parameters are shown in Table 1. Table 1 shows the design parameters of the comparative examples and the examples.

[0053] The cycle attenuation rate is the percentage of the initial capacity of the battery cell when it is charged to 4.5V at 3.5C step rate and charged to the cut-off voltage at 1.5C, and the capacity remains after 800 cycles.

[0054] Rate performance is the ratio of the 2C rate discharge capacity to the 0.2C rate discharge capacity of the battery cell at room temperature.

[0055] The charging window is the maximum rate at which the battery cell will not deposit lithium after the cell interface is disassembled at the cut-off voltage under 3.5C, 3.2C, 3.0C, 2.8C, 2.6C, 2.4C, and 2.0C conditions.

[0056] Table 1

[0057]

[0058] In the above table: D3 is the thickness of the active material layer when only one layer of active material is coated, and P is the degree of graphitization when only one layer of active material is coated.

[0059] From the comparison between Examples 1 and 3 and Comparative Examples 1 and 3, it can be seen that when the depth of the recess satisfies D2≤D<D2+1 / 2D1, the capacity attenuation rate, rate performance and maximum rate of the battery cell are greatly improved.

[0060] From the comparison between Example 2 and Comparative Example 2, it can be seen that even if the first active material layer and the second active material layer are both set to have a high degree of graphitization, the improvement on the capacity attenuation rate, rate performance and maximum rate of the battery cell is small. Due to the need for drilling, part of the second active material layer material is removed during the drilling, which makes the utilization rate of the second active material layer material small. In addition, since the electrolyte infiltration effect of the second active material layer is better, increasing the degree of graphitization of the second active material layer has little effect on the improvement of the charge and discharge performance of the second active material layer.

[0061] Example 4

[0062] Positive electrode sheet: The active material lithium cobalt oxide, the conductive agent acetylene black, the conductive carbon nanotubes, and the binder polyvinylidene fluoride (PVDF) are fully dispersed and evenly coated on the aluminum current collector in an N-methylpyrrolidone solvent system in a weight ratio of 97.8:0.6:0.4:1.2, and then cold-pressed and sliced ​​to obtain the positive electrode sheet.

[0063] Negative electrode sheet: The negative electrode active material with a graphitization degree of 95% and the negative electrode active material with a graphitization degree of 99% were mixed with sodium methyl cellulose and styrene-butadiene rubber (SBR) emulsion in a weight ratio of 97.7:11:12 to prepare two negative electrode active material slurries, which were simultaneously coated on the copper current collector. The thickness of the surface active material with a graphitization degree of 95% was 15μm and the thickness of the bottom active material with a graphitization degree of 99% was 30μm. Then, the negative electrode sheet was obtained by cold pressing and striping. The laser drilling parameters of the electrode sheet were: depth 20μm, aperture 75μm, and spacing 2.5mm.

[0064] Isolation film: The PE surface is coated with a ceramic mixture as an isolation film.

[0065] Electrolyte: Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a volume ratio of 1:1:4:4, and then fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0066] Preparation of a full battery: The positive electrode sheet, separator, and negative electrode sheet are wound or stacked to produce a bare cell, which is then packaged and injected with electrolyte to produce a finished lithium-ion battery.

[0067] The batteries of Examples 5 to 12 and Comparative Examples 4 to 7 were prepared in a similar manner to Example 4, and the specific parameters are shown in Table 2. Table 2 shows the design parameters of the comparative examples and the examples.

[0068] Local volume loss rate: the ratio of the volume of the material removed from the recess to the volume of the entire negative electrode sheet.

[0069] The cycle attenuation rate is the percentage of the initial capacity of the battery cell when it is charged to 4.5V at 3.5C step rate and charged to the cut-off voltage at 1.5C, and the capacity remains after 800 cycles.

[0070] Rate performance is the ratio of the 2C rate discharge capacity to the 0.2C rate discharge capacity of the battery cell at room temperature.

[0071] The charging window is the maximum rate at which the battery cell will not deposit lithium after the cell interface is disassembled at the cut-off voltage under 3.5C, 3.2C, 3.0C, 2.8C, 2.6C, 2.4C, and 2.0C conditions.

[0072] Table 2

[0073]

[0074]

[0075] The hole depths of Examples 4-12 all meet the requirement of D2≤D<D2+1 / 2D1, while the hole depths in the comparative examples are not particularly limited.

[0076] It can be seen from Comparative Examples 4-7 that the capacity attenuation rate, rate performance and maximum rate of the comparative examples have large fluctuations, and the charge and discharge performance of the electrode cannot be effectively and reasonably controlled.

[0077] By comparing Examples 4-12 with Comparative Examples 4-7, the following results were obtained:

[0078] It can be seen from the table that when the pore depth is too deep, the pore diameter is too large, and the spacing is too wide, the degree of graphite damage is more serious, which affects the lithium insertion rate of the lithium-ion battery, resulting in lithium precipitation, which in turn affects the cycle.

[0079] By comparing Example 4 with Comparative Example 7, it can be seen that setting the first active material layer to have a high degree of graphitization can improve conductivity, which is beneficial to the deintercalation of lithium ions. The layered structure of graphite is beneficial to the migration of lithium ions. A high degree of graphitization can increase the migration speed of lithium ions and improve the rate performance of the battery. In addition, since the transmission of lithium ions is accelerated, lithium ions can be deintercalated in time, which can prevent capacity decay caused by lithium ion deposition and improve the capacity decay rate. By comparing Example 12 with Comparative Example 7, it can be seen that setting the second active material layer to have a low degree of graphitization has little effect on the overall performance of the battery, and the cost can be reduced by setting the second active material layer to have a low degree of graphitization.

[0080] By comparing Example 4 and Comparative Example 5, it can be seen that when the spacing between the recesses is too large and the local volume loss rate is too small, since there are too few recesses, it is impossible to improve the lithium ion transmission coefficient and reduce the lithium ion transmission resistance, and it is impossible to reduce lithium deposition on the electrode surface, and the maximum rate is small.

[0081] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.

Claims

1. A negative electrode plate, characterized in that: It comprises a current collector (1), and a first active material layer (2) and a second active material layer (3) which are sequentially coated on the surface of the current collector (1) and have different graphitization degrees, and the graphitization degree of the first active material layer (2) is greater than the graphitization degree of the second active material layer (3); It also comprises a plurality of evenly distributed recesses (4), wherein in the thickness direction of the current collector (1), the plurality of recesses (4) penetrate the second active material layer (3) and extend into the interior of the first active material layer (2); The average thickness of the first active material layer (2) is D1, the average thickness of the second active material layer (3) is D2, and the depth of the recess (4) is D, and the relationship between them satisfies: D2≤D<D2+1 / 2D1.

2. The negative electrode sheet according to claim 1, characterized in that: The graphitization degree of the first active material layer (2) is P1, and the graphitization degree of the second active material layer (3) is P2, and the relationship between them satisfies: 0.9<P2<P1; the depth D of the concave portion (4) satisfies: D2≤D<D2+1 / 3D1.

3. The negative electrode sheet according to claim 1, characterized in that: The volume of the material removed from the recess (4) is less than or equal to 20% of the volume of the entire negative electrode plate.

4. The negative electrode sheet according to claim 3, characterized in that: The volume of the material removed from the recess (4) is greater than 5% of the volume of the entire pole piece.

5. The negative electrode sheet according to claim 1, characterized in that: The recesses (4) are arranged in a regular structure or an irregular structure, and the distance between two adjacent recesses (4) is less than 2.5 mm.

6. The negative electrode sheet according to claim 5, characterized in that: The recess (4) is arranged to be a regular circular, square, elliptical or conical structure.

7. The negative electrode sheet according to claim 6, characterized in that: When the recess (4) is arranged as a circular regular structure, the aperture of the recess (4) is less than 80 μm.

8. The negative electrode plate according to claim 1, characterized in that: The depth D of the recess (4) is 10 μm to 50 μm.

9. The negative electrode sheet according to claim 1, characterized in that: The surface of the current collector (1) is also coated with a functional layer (5) adjacent to the first active material layer (2).

10. A battery, characterized in that: The negative electrode sheet comprises the negative electrode sheet as described in any one of claims 1 to 9.